Forced Execution of the Object of Fiduciary Guarantees Through the Debt Collector - Shobirin, Shobirin; Harahap, Mhd. Yadi; Musaddat, Anwar; Aulia, Syahwa Nur; Syakilah, Nadra Putri; Siregar, Nur Aini (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
To achieve national goals, economic sector activities have the main aim of improving the standard of living and welfare of the community, and various policies are implemented to reactivate economic activities and give business entities more freedom to develop their businesses. One of the government policies to encourage development and economic growth is credit. To guarantee loan repayment from the borrower, the lender must have collateral, and one of the collaterals used is a fiduciary guarantee.